Allosteric binding on nuclear receptors: Insights on screening of non-competitive endocrine-disrupting chemicals. (15th January 2022) - Zhang, Chi; Wu, Jinqiu; Chen, Qinchang; Tan, Haoyue; Huang, Fuyan; Guo, Jing; Zhang, Xiaowei; Yu, Hongxia; Shi, Wei
Highlights: EDCs can interact with NRs at allosteric sites. Allosteric sites are distributed in multi-domains and engaged in function-related interactions of NRs. Experimental and computational simulation methods were sorted out for allosteric site recognition and mechanism insight. Abstract: Endocrine-disrupting chemicals (EDCs) can compete with endogenous hormones and bind to the orthosteric site of nuclear receptors (NRs), affecting normal endocrine system function and causing severe symptoms. Recently, a series of pharmaceuticals and personal care products (PPCPs) have been discovered to bind to the allosteric sites of NRs and induce similar effects. However, it remains unclear how diverse EDCs work in this new way. Therefore, we have systematically summarized the allosteric sites and underlying mechanisms based on existing studies, mainly regarding drugs belonging to the PPCP class. Advanced methods, classified as structural biology, biochemistry and computational simulation, together with their advantages and hurdles for allosteric site recognition and mechanism insight have also been described. Furthermore, we have highlighted two available strategies for virtual screening of numerous EDCs, relying on the structural features of allosteric sites and lead compounds, respectively. We aim to provide reliable theoretical and technical support for a broader view of various allosteric interactions between EDCs and NRs, and to drive high-throughput and accurate screening of potential EDCs with non-competitive effects.